Implementation of Cooperative Learning Method in The Nurul Huda Islamic Kindergarten Samarinda - Rasyid, Nurbiah; Malik, Lina Revilla (EDUCASIA: Jurnal Pendidikan, Pengajaran, dan Pembelajaran, 2024)
The cooperative learning method is one of the methods that can be used for early childhood. This method can holistically support early childhood development. One of the kindergartens that apply the cooperative learning method is Nurul Huda Islamic Kindergarten Samarinda. For this reason, it is necessary to see how the cooperative learning method is implemented at Nurul Huda Islamic Kindergarten Samarinda. This research uses a qualitative approach, and data collection techniques are carried out through observation, interviews, and documentation. The data is then found in the analyst with data triangulation and descriptive narrative. The results showed that facilities and infrastructure supported the implementation of the cooperative learning method well. However, there is still a challenge, namely at the beginning of early childhood learning, that is egocentric, so it is necessary for the role of teachers to have good classroom management and to be an example when the method is implemented.